Microstructure and mechanical properties of TiC steel-bonded carbides prepared by two-step sintering technique. (December 2020) - Guo, Xiaoge; Zheng, Yong; Zhang, Guotao; Wu, Hao; Yang, Zhengkai; Gong, Ao
Abstract: In this study, a two-step sintering technique was applied to prepare TiC steel-bonded carbides. The first step sintering process was heating to a liquid sintering temperature of 1390 °C without soaking time for achieving a critical density, and then unstable micropores remained in the samples, in which the rapidly densification of sample primarily depended on liquid pore filling. The second step sintering was performed at a lower temperature of 1330 °C for 10 h to complete densification process due to the grain-boundary diffusion. Compared with traditional vacuum sintering method, the growth of TiC particle was inhibited significantly and the evaporation of metal binder was suppressed through the two-step sintering technique. Overall, the prepared samples possessed excellent mechanical properties with the TRS and hardness of 2093.3 MPa and 87.3 HRA, respectively. Highlights: Two-step sintering technique was applied to prepare dense TiC steel-bonded carbides. The effects of two step sintering parameters on microstructures of TiC steel-bonded carbides were investigated. The TiC particle growth was inhibited and relative density increased further during the second step sintering. The TiC steel-bonded carbides possessed excellent mechanical properties.